Risk of new-onset and recurrent uveitis with different biologics for ankylosing spondylitis: a network meta-analysis - Zhao, Xu; Xie, Qingqing; He, Xinyi; Lu, Yiwei; Li, Menglan; Shuai, Shiquan (Frontiers in Immunology, 2025)
BackgroundUveitis is a common extra-articular manifestation of ankylosing spondylitis (AS), and a systematic analysis of the effects of biologics on new-onset and recurrent uveitis is clinically important.MethodsWe conducted a network meta-analysis (NMA) to assess the impact of anti-TNF-α (adalimumab, etanercept, golimumab, and infliximab), IL-17 inhibitors (secukinumab, bimekizumab, and ixekizumab), and JAK inhibitors (tofacitinib and upadacitinib) on new-onset and recurrent uveitis. Phase II/III double-blind randomized controlled trials and cohort studies were included. The relative risk (RR) was estimated, and drug efficacy was ranked based on the surface under the cumulative ranking curve (SUCRA).ResultsA total of 17 articles with 18 studies and 11,529 AS patients were included. For new-onset uveitis, adalimumab reduced the risk significantly compared to etanercept and golimumab (RR: 0.30, 0.61), while etanercept increased the risk compared to golimumab and infliximab (RR: 2.03, 2.47). The SUCRA demonstrated that upadacitinib (84.0%) exhibited better efficacy, while ixekizumab (8.7%) was less effective than placebo (29.9%). For recurrent uveitis, adalimumab significantly reduced the risk compared to etanercept (RR: 0.70), while etanercept increased the risk compared to golimumab and infliximab (RR: 1.37, 1.70). Bimekizumab 160 mg and 320 mg were the most efficacious (SUCRA: 83.9%, 83.5%). A comprehensive analysis revealed that bimekizumab 320 mg and 160 mg were the most effective in reducing the incidence of uveitis. Ixekizumab and secukinumab were less effective than placebo.ConclusionJAK inhibitors were more effective for new-onset uveitis in AS patients. Inhibition of IL-17A (secukinumab and ixekizumab) alone might increase the risk of uveitis, while simultaneous inhibition of IL-17A and IL-17F (bimekizumab) significantly reduced the risk. Etanercept increased the risk of uveitis compared to other TNF-α inhibitors.